KAJIAN PENGETAHUAN, SIKAP, DAN TINDAKAN MASYARAKAT DALAM MEWASPADAI GIGITAN ANJING SEBAGAI HEWAN PENULAR RABIES (HPR) DI KOTA BANDA ACEH (Study of Knowledge, Attitude, and Practice of the Community in Four Sub-Districts in Banda Aceh for Their Preparedness of Dogs Attacking as Rabies Risk Animals) - Muhammad Parwis; Teuku Reza Ferasyi; Muhammad Hambal; Dasrul Dasrul; Razali Razali; Andi Novita (Jurnal Medika Veterinaria, 2016)
This research was aimed to study the number of cases attacking by dog as rabies risk animals (RRA) and the level of knowledge, attitude, and practice of the community in four sub-districts of Banda Aceh. The study was conducted using survey method by interviewing 60 respondents with structured questionnaire. The results of this research showed that respondent or their relatives which had been bitten by RRA was 26.7%-30.0%. The level of respondent knowledge to rabies in these two categories area can be categorized as moderate (76.6%). The attitude of respondent in preparedness of RRA was categorized as good (90-96.7%). Then, the practice of respondent in preparedness of RRA was categorized as moderate (83.3-96.7%). It is concluded that the level of knowledge, attitude, and practice of the community in those two categories sub-districts is at moderate level.